2014
DOI: 10.1118/1.4898594
|View full text |Cite
|
Sign up to set email alerts
|

Does administering iodine in radiological procedures increase patient doses?

Abstract: Adding iodine can result in values of localized absorbed dose increasing by more than an order of magnitude, but the total energy deposition is generally very modest (i.e., <10%). Their data show that adding iodine primarily changes the pattern of energy deposition in the irradiated region, rather than increasing patient doses per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The dosimetry performed in this study did not consider the presence of barium in the patient, which may affect the resultant patient doses. A recent study (He et al, 2014) investigated the effect of adding iodine to patient doses, which is likely to be applicable to barium given the close similarity between Iodine (Z = 53; k-edge 33 keV) and barium (Z = 56; k-edge 37 keV). In this study, the addition of iodine was found to have negligible effects on absorbed tissue doses at locations that are in front of the added iodine, but that substantial dose reductions can occur at x-ray beam locations that are behind the added contrast material.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetry performed in this study did not consider the presence of barium in the patient, which may affect the resultant patient doses. A recent study (He et al, 2014) investigated the effect of adding iodine to patient doses, which is likely to be applicable to barium given the close similarity between Iodine (Z = 53; k-edge 33 keV) and barium (Z = 56; k-edge 37 keV). In this study, the addition of iodine was found to have negligible effects on absorbed tissue doses at locations that are in front of the added iodine, but that substantial dose reductions can occur at x-ray beam locations that are behind the added contrast material.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study by Amaton et al [19] also identified that inclusion of iodine contrast media in CT scans results in direct dose enhancement specific to various organs ranging from 20% to 70%. In addition, a recent Monte Carlo simulation based study conducted by He et al [20] also demonstrated an increase in dose caused by micro-spheres containing contrast media in a modelled phantom. Whilst these studies indicate (or suggest) that contrast media does have both a direct and indirect impact on CT dose, there is a need to theoretically and experimentally examine and quantify the direct effects of contrast media on CTDI.…”
Section: Introductionmentioning
confidence: 87%
“…Three groups of researchers have investigated the impact of ICM on the absorbed dose to tissues other than the blood, from diagnostic x-ray procedures [6][7][8][9][10], albeit with very different approaches. Amato et al [6,7]…”
Section: Model Region (Figure 4 Region)mentioning
confidence: 99%
“…x-ray imaging have been published [6][7][8][9][10]. These have generally focused on macroscopic doses, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation